Implementasi model problem based learning dengan KODIGORO terhadap hasil belajar Pendidikan Pancasila di Kelas IV SDN 2 Keling Jepara - Nadia Kamila Putri; Ika Ari Pratiwi; Much Arsyad Fardani (COLLASE (Creative of Learning Students Elementary Education), 2026)
This study aims to examine the implementation of the Problem Based Learning (PBL) model assisted by KODIGORO digital comic media in improving learning outcomes for Pancasila Education in grade IV students of SDN 2 Keling. The background of the study was the low learning outcomes of students in the pre-study due to the inappropriateness of the learning model and media used. PBL was chosen because it is student-centered and encourages solving real problems, while KODIGORO digital comics are considered effective in conveying the values ​​of mutual cooperation in an interesting and easy-to-understand manner. The research method uses a quantitative approach with a one-group pre-test post-test design. Data collection techniques include observation, interviews, tests, and documentation, and are analyzed using normality, homogeneity, and N-gain tests. The results of the study showed an increase in learning outcomes in all indicators, especially in understanding and applying the values ​​of mutual cooperation. The implications of this study indicate that the use of the PBL model combined with the digital comic KODIGORO can be an effective alternative learning strategy to improve learning outcomes and internalize Pancasila values ​​from an early age, particularly the value of mutual cooperation. This model is recommended for wider application in Pancasila Education learning at the elementary school level. Keywords: PBL Model, KODIGORO Game Media, and Learning Outcomes